Search 70,667 tutors

# How do I solve Algebra Equation (x+2) (x+3)=0?

This is a quadratic equation.  Normally, you'll probably be given something that looks like x^2 + 2x - 5 = 0.  Then you'd have to factor the equation to solve. Here, you're lucky - it's already factored!  That means we just need to set each of the two parts equal to zero, and solve each part.  Remember you can have 2 answers to a quadratic equation!

(x-2)(x+3) = 0

(x-2) = 0   OR (x+3)=0
x-2+2 = 0+2  OR x+3-3 = 0-3
x = 2  OR x = -3

Our two answers are x= 2 and x=-3.  This is commonly written as x={2,-3}.

Good luck!

this is already factored.  use the zero product rule:  if ab=0, then a=0, and b=0

therefore, if (x+2)(x+3)=0,   let x+2=0,  subtract 2 from each side, and x+2-2 = 0-2,  and x = -2

then let the other factor equal 0:  let x+3 =0,  subtract 3 from each side,  x+3-3 = 0-3  and. x = -3

therefore x = -2,  and. x = -3

(x+2)(x+3)              - Original Equation

x^2 + 2x +3x + 6     - FOIL

If you are solving for X you have to isolate each factor and set it equal to 0

Solve the factor of (X+2) first

x+2=0

(x+2) -2= 0-2        subtract 2 from both sides

Now solve the factor of (x+3)

(x+3) = 0

x+3-3= 0-3        subtract 3 from both sides